2008
DOI: 10.1186/1476-4598-7-32
|View full text |Cite
|
Sign up to set email alerts
|

DNA-dependent protein kinase catalytic subunit modulates the stability of c-Myc oncoprotein

Abstract: BackgroundC-Myc is a short-lived oncoprotein that is destroyed by ubiquitin-mediated proteolysis. Dysregulated accumulation of c-Myc commonly occurs in human cancers. Some of those cases with the dysregulated c-Myc protein accumulation are attributed to gene amplification or increased mRNA expression. However, the abnormal accumulation of c-Myc protein is also a common finding in human cancers with normal copy number and transcription level of c-Myc gene. It seems that the mechanistic dysregulation in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 43 publications
4
53
0
Order By: Relevance
“…All of the antibodies are commercially available: anti-DNA-PKcs total (sc-9051, H163, Santa Cruz), anti-phosphor- siRNAs and transfection. For the knockdown of Ku70 and Ku80 expression, the siRNA molecules used are adopted from previous reports: annealed Ku70 siRNAs sense strand 5′-GGAAGAGAUAGUUUGAUUUdTdT-3′, antisense strand 5′-AAAUCAAACUAUCUCUUCCTG-3′ (33); Ku80 siRNAs sense strand 5′-ACAAAAUCCAGCCAAGUUCdTdT-3′, antisense strand 5′-GAACUUGGCUGGAUUUUGUTG-3′ (34); and the silencer negative control siRNA sense strand 5′-UUCUCC-GAACGUGUCACGUTT-3′ (32). The siRNA molecules were synthesized and purified by Shanghai GenePharma Co.; siRNA transfection was performed using Lipofectamine 2000 reagent according to the procedures reported (32).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the antibodies are commercially available: anti-DNA-PKcs total (sc-9051, H163, Santa Cruz), anti-phosphor- siRNAs and transfection. For the knockdown of Ku70 and Ku80 expression, the siRNA molecules used are adopted from previous reports: annealed Ku70 siRNAs sense strand 5′-GGAAGAGAUAGUUUGAUUUdTdT-3′, antisense strand 5′-AAAUCAAACUAUCUCUUCCTG-3′ (33); Ku80 siRNAs sense strand 5′-ACAAAAUCCAGCCAAGUUCdTdT-3′, antisense strand 5′-GAACUUGGCUGGAUUUUGUTG-3′ (34); and the silencer negative control siRNA sense strand 5′-UUCUCC-GAACGUGUCACGUTT-3′ (32). The siRNA molecules were synthesized and purified by Shanghai GenePharma Co.; siRNA transfection was performed using Lipofectamine 2000 reagent according to the procedures reported (32).…”
Section: Methodsmentioning
confidence: 99%
“…HeLa, HeLa-NC, HeLa-H1, and ATM-deficient AT5BIVA cells were maintained in DMEM containing 10% fetal bovine serum, 100 units/mL penicillin, and 100 μg/mL streptomycin in a humidified incubator at 37°C in 5% CO 2 . HeLa-H1 and HeLa-NC were generated from HeLa cells by stably transfecting with a DNA-PKcs-specific siRNA construct targeting the catalytic motif (nucleotides 11637-11655, H1) and a control siRNA construct (NC), respectively (32). A cobalt-60 γ-ray source was used to irradiate the cells at a dose rate of 1.74 Gy/min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…These results suggest that the interaction between DNA-PKcs and c-Myc provides a DNA damage-responsive complex through which c-Myc may be directly involved in DSB repair. At the same time, DNAPKcs regulates the stability of c-Myc [21], but c-Myc may also act as a weak inhibitor to regulate the autophosphorylation of DNA-PKcs at S2056. It has been reported that the autophosphorylation of DNA-PKcs causes DNA-PKcs to separate from Ku, which inhibits the catalytic activity of DNA-PK [34].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous work, we found that the DNA-dependent protein kinase catalytic subunit (DNA-PKcs) and c-Myc proteins interact with each other, and we proposed a new signalling pathway for maintaining the stability of c-Myc, the DNA-PKcs/Akt/GSK3/c-Myc pathway [20,21]. DNAPKcs is a protein kinase requiring DNA ends as a cofactor, and it is thus also known as the DNA break-sensing molecule, which is crucial in the non-homologous end joining (NHEJ) pathway of DNA DSB repair [22,23].…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly, previous studies demonstrated that c-Myc interacts with DNA-PKcs (28) and that the inactivation of DNA-PKcs results in a marked reduction of c-Myc protein expression via the ubiquitin/ proteasome pathway (29,30). We examined whether MeV infection and the consequent DNA-PK inactivation also induce c-Myc degradation.…”
Section: Resultsmentioning
confidence: 99%